THE ROLE OF FISHERIES INDUSTRY IN THE ECONOMY OF LAMPUNG PROVINCE: AN INPUTâOUTPUT ANALYSIS - , Gusrizal, Professor Takahiro Akita ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aimed to examine the industrial structure of Lampung with particular focus on fisheries and fish and shrimp processing industry, trade pattern of Lampung, the contribution of fisheries and fish and shrimp processing industry to the economy of Lampung by using simple output multiplier and simple household income multiplier, as well as to examine the inter-sectoral linkages. In order to examine the inter-sectoral linkages, this study calculates backward and forward linkages. The data used in this study relies mostly on the input-output table of Lampung in 2000. The industrial structure showed that the fish and shrimp processing industry had a small figure. In line with fish and shrimp processing industry, fisheries subsector that comprised marine fisheries, inland fisheries and shrimp also showed the small figures although its location quotient (LQ) showed the figure more than 2. It means that fish and shrimp processing industry has not changed the industrial structure of Lampung Province yet. In addition, the calculation of contribution of fish and shrimp processing industry to the economy of Lampung by using multipliers showed that it had the highest figure in the simple output multiplier. Regarding the inter-sectoral linkages by using backward linkage and forward linkage, fish and shrimp processing industry showed high backward linkage both direct backward linkage and total backward linkage. It means that fish and shrimp processing industry had good relation with the fisheries sub-sector (marine fisheries, inland fisheries, and shrimp) as the provider of inputs for the fish and shrimp processing industry. On the other hand, fish and shrimp processing industry showed a low forward linkage both direct forward linkage and total forward linkage. This study proposes recommendations to the Lampung local government should pay more attention to fisheries and fish and shrimp processing industry by looking for a good solution to solve the problems of fisheries and fish and shrimp industry in order to develop those sectors well. In addition, fisheries, fish and shrimp processing industry and other sectors should be reinforced by the Lampung local government to develop the economic development.